Pengaruh Model Pembelajaran Koopratif Tipe Inside Circle (IOC) terhadap Motivasi Belajar IPA di Kelas V SD Muhammadiyah O3 Medan - Annisa, Annisa; Pratiwi, Indah (EduInovasi: Journal of Basic Educational Studies, 2024)
The use of a learning model really determines success in the learning process, for this reason it is necessary to design a learning model that provides opportunities for students to be more active and build the nature of cooperation in groups so that students are motivated in learning. One learning model that can be used in learning is the inside outside circle learning model. The problem formulation in this research is whether there is an influence of the inside outside circle learning model on students' learning motivation in science subjects at SD Muhamadiyah 03 Medan. The research method used in this research is a quasi-experimental method. This research was carried out on Jl. Abdul Hakim No.2, Tj. Sari, District. Medan Selayang, Medan City. Which consists of 1 class which is divided into experimental class and control class. Data collection techniques are questionnaires, observations and interviews. The data analysis technique uses the Liliefors test to test the normality of the data, the Fisher test to test the homogeneity of variance and the t-test to test the hypothesis. The observed aspect of learning motivation has increased with the average obtained from the five indicators of learning motivation in the Pretest of 72.87 increasing to Posttest 85.03. which means Ha is accepted and H0 is rejected. Based on the research results, it shows that there is an influence of the inside outside circle learning model on the learning motivation of class V students in science subjects in Class V of SD Muhammadiyah 03 Medan.